KORELASI KETERAMPILAN MEMBACA APRESIATIF DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XI SMA ADABIAH 2 PADANG - Apriyenti, Lisa; Tressyalina, Tressyalina (Universitas Negeri Padang, 2020)
ABSTRACTÂ The purpose of this research was to describe things as follows. First, describes the skills of reading appreciative grade XI Senior High School 2 Padang. Second, it describes the writing skills text cerpen grade XI Senior High School 2 Padang. Third, explain the relationship between the reading appreciative with writing skill text cerpen grade XI Senior High School 2 Padang. This type of research correlation between appreciative reading skills and writing skills text cerpen of grade XI Senior High School 2 Padang is quantitative research with descriptive methods. Based on the reslt of the study, the following three things concluded. First, the appreciative reading skills of grade XI Senior High School 2 Padang are in good qualification (81,32). Second, the writing skills text cerpen on grade XI Senior High school 2 Padang are in good qalification (82.24). Third, there is a significant correlation between appreciative reading skills and writing skills text cerpen of grade XI Senior High School 2 Padang at n-1 degress freedom and a sicnificant level of 95%.Â Kata Kunci: korelasi, membaca apresiatif, menulis teks cerpen